IMPLEMENTASI KURIKULUM 2013 DI MADRASAH IBTIDAIYAH KAHASRI KOTA PROBOLINGGO: Implementation Of Curriculum 2013 In Elementary School Kahasri Probolinggo - Allifatur Rohma (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2019)
Madrasah Ibtidaiyah of KAHASRI is an institution appointed by the Indonesian Ministry of Religion to implement the 2013 Curriculum or called K13 both in thematic and religious learning, which is in line with the Decree of the Director of Islamic Education Number 3525 in 2017 about Determination of the Implementation of the 2013 Curriculum. This research focused on the implementation of 2013 curriculum management. This research used a qualitative approach, and the type was a case study. The determination of research subjects was purposive. Data collection techniques were interviews, observation, and documentation. Interactive data analysis used the Miles and Huberman model, with the following steps; condensation, data presentation, and verification. The results of this research reveal that; 1) learning design of k13 is the teacher in Madrasah Ibtidaiyah KAHASRI of Probolinggo make learning tools such as Educational Calendar, RPE, Prota, Promissory Notes, Syllabus, and RPP. In making learning tools, there is a teacher who makes individually and together KKG (Teacher Working Group). 2) the implementation of K13 learning in Madrasah Ibtidaiyah KAHASRI of Probolinggo has three activities: introduction, essence, and closing. The introduction is preceded by giving apperception, giving motivation, delivering purpose, and the benefit of learning. In the essence activity, the teacher had done scientific activities such as; observing, asking questions, trying, associating/collecting, and communicating. In closing, the teacher concluded the material given and gave the task. (3) Evaluation of K13 learning in Madrasah Ibtidaiyah KAHASRI of Probolinggo used authentic assessment models including three aspects; aspects of attitude, aspects of knowledge, and aspects of skills.